Dynamic response of a pneumatic pressure valve applied to the design of an actuation system in assistive robotics - Lescano Pastor, Claudia Noemí (2015)
This work describes the dynamics of a propor-tional pressure regulator valve, with views to its application to control a pneumatic artificial muscle used as active element of an ankle-foot orthosis for gait rehabilitation. A valve linear model that considers the effect on the valve output pressure of its reference input voltage was obtained and analyzed in the frequency domain applying the following methodology. By means of an experimental setup and for different reference input signals at 0.4-1.5 Hz frequency range, the pressure re-sponse was first evaluated, obtaining then an open loop trans-fer function characterizing the valve pressure – reference voltage relation. Finally, the achieved results were validated and discussed under the framework of its linear approach and the intended application, related with the design of an actua-tion system in assistive robotics.